Mediterranean fruit fly subplot hot spots prediction by experts' experience. (11th January 2018) - Mendelsohn, O.; Dayan, T.; Aidlin‐Harari, S.; Silberstein, M.; Orlov, V.; Blank, L.
Abstract: The Mediterranean fruit fly (medfly), Ceratitis capitata (Wiedemann), is a major pest, infesting hundreds of crop types. Since current field monitoring is mostly manual, understanding the spatiotemporal patterns of pest emergence at the fine scale can optimize precise trap placement and site‐specific treatment activities, also within area wide integrated pest management projects. We carried out a three‐year study in deciduous orchards in Israel, testing for the existence of subplot hot spots in which medfly populations display small‐scale aggregations over consecutive seasons, beyond the expected spatial variability resulting from host type and ripening sequence. medfly population increase in these locations often preceded or was parallel to infestations in surrounding orchards, suggesting that hot spots can provide an important tool for effective prediction and control of pest emergence. We also examined the use of expert knowledge to predict hot spot locations and suggest a methodology for verifying them.